An efficient usage rate biclustering algorithm in real-valued function-resource dataset. Issue 3 (September 2017) - Wang, Miao; Zhang, Lihua; Xiong, Zhiyong; Yang, Tao
Task synthesis, function fusion, and resource integration are used to get higher performance and more reliability in integrated modular avionics system. However, safety issue is caused in the system integration process. In order to discover the potential hazards for function layer safety analysis, in this paper, we proposed an efficient biclustering algorithm— DeCluster, which can effectively mine all biclusters with maximal variant usage rate or maximal low usage rate in real-valued function-resource dataset. First, it constructs a sample weighted graph, which contains all resource relations set between two samples that satisfy the definitions; second, all maximal variant usage rate or low usage rate biclusters are mined in the graph. In order to get higher the mining efficiency of the algorithm, DeCluster algorithm uses several pruning strategies. The experimental results show our algorithm is more efficient.